DIABETES INSIPIDUS: LITTLE-KNOWN FACTS - L. Yu. Morgunov (Исследования и практика в медицине)
The most common causes of diabetes insipidus are neurosurgical operations on the pituitary gland due to its defeat by benign and malignant tumors, the neoplasms themselves, lymphocytic hypophysitis. Much less is known about the development of metastatic lesions of the pituitary gland by primary tumors of the lung, breast and kidneys. Even less common is diabetes insipidus caused by leukemia, lymphoma, xanthogranulomas, germinomas, HIV infection, pituitary hemorrhage, drug-induced, combined with neurofibromatosis, as well as diabetes insipidus during pregnancy. The review describes the predictors of the development of diabetes insipidus during surgical interventions, the frequency of development and prognosis in various neurosurgical operations. The article focuses doctors of various specialties on timely diagnosis, prevention and treatment of diabetes insipidus, including its atypical forms.